2009
DOI: 10.5194/nhess-9-539-2009
|View full text |Cite
|
Sign up to set email alerts
|

Ground effects and hydrological changes in the Southern Apennines (Italy) in response to the 23 July 1930 earthquake (<i>M<sub>S</sub></i>=6.7)

Abstract: Abstract. The 23 July 1930 earthquake (M S =6.7) in the Southern Apennines (Italy) was a catastrophic event that produced many effects such as surface faulting, fractures, landslides, settlements, hydrological changes, variations in chemical/physical activity related to the volcanic and/or thermal zones and also acoustic and optical phenomena. It is the first great earthquake of the twentieth century that was studied, thanks to the hydrological monitoring network of the Italian Hydrographic Survey (IHS) set up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Episodes of high discharge are correlated with seismic activity having features similar to tremor but are not correlated with large regional earthquakes (Brown et al, 2005). Data shown with circles are from the compilation in Wang and Manga (2010a) with additional data shown with squares for the M8.8 Maule earthquake of 2010 (Mohr et al, 2012), the Tasso and Tanagro river responses to the M6.7 Irpinia, Italy, earthquake of 1930 (Esposito et al, 2009), and spring responses to the M5.9 Draney Peak, the United States, earthquake of 1994 (Schuster and Murphy, 1996). Data shown with circles are from the compilation in Wang and Manga (2010a) with additional data shown with squares for the M8.8 Maule earthquake of 2010 (Mohr et al, 2012), the Tasso and Tanagro river responses to the M6.7 Irpinia, Italy, earthquake of 1930 (Esposito et al, 2009), and spring responses to the M5.9 Draney Peak, the United States, earthquake of 1994 (Schuster and Murphy, 1996).…”
Section: Fault Valves and Ruptured Subsurface Reservoirsmentioning
confidence: 99%
“…Episodes of high discharge are correlated with seismic activity having features similar to tremor but are not correlated with large regional earthquakes (Brown et al, 2005). Data shown with circles are from the compilation in Wang and Manga (2010a) with additional data shown with squares for the M8.8 Maule earthquake of 2010 (Mohr et al, 2012), the Tasso and Tanagro river responses to the M6.7 Irpinia, Italy, earthquake of 1930 (Esposito et al, 2009), and spring responses to the M5.9 Draney Peak, the United States, earthquake of 1994 (Schuster and Murphy, 1996). Data shown with circles are from the compilation in Wang and Manga (2010a) with additional data shown with squares for the M8.8 Maule earthquake of 2010 (Mohr et al, 2012), the Tasso and Tanagro river responses to the M6.7 Irpinia, Italy, earthquake of 1930 (Esposito et al, 2009), and spring responses to the M5.9 Draney Peak, the United States, earthquake of 1994 (Schuster and Murphy, 1996).…”
Section: Fault Valves and Ruptured Subsurface Reservoirsmentioning
confidence: 99%
“…The fault plane orientation was WNW-ESE (Apennine chain trend), the fault length was 32.6 km and the depth 15 km, estimated on the basis of the equivalent ray of the major isoseismal lines (Gasperini et al, 1999). Hydrological changes were observed in the whole macroseismic field, mostly in the far field, near the main carbonate aquifers in a widespread karstic environment (Esposito et al, 2009 . Spring flow at Madonna del Carmine increased from 10 l/min to 40 l/min after the earthquake, and at Monte della Guardia increased from 5 l/min to 16 l/min at the end of August (Esposito et al, 2009).…”
Section: The Earthquake Of July 1930mentioning
confidence: 99%
“…Hydrological changes were observed in the whole macroseismic field, mostly in the far field, near the main carbonate aquifers in a widespread karstic environment (Esposito et al, 2009 . Spring flow at Madonna del Carmine increased from 10 l/min to 40 l/min after the earthquake, and at Monte della Guardia increased from 5 l/min to 16 l/min at the end of August (Esposito et al, 2009). At Solfatara, a volcanic crater in Pozzuoli (near Neaples), at a distance of about 100 km from the epicentre, variations in endogenous activity were observed for about 20 days after the earthquake.…”
Section: The Earthquake Of July 1930mentioning
confidence: 99%
“…On the other hand, [26] recognized during the well-known Loma Prieta earthquake, significant hydrological changes in two basins located near field from San Andreas Fault, attributing the cause of these modifications to the formation of new fractures capable to develop novel continuous flow path or enhance existing continuous flow path. In Italy, some authors suggested different interpretations to explain groundwater modifications due to the main earthquakes occurred in the country [27][28][29][30]. As concerns the strongest earthquake occurred in Italy during the Amatrice-Norcia seismic sequence (August 2016-January 2017), some models were in fact proposed to justify the spring and river discharge change occurred in the area [11,31,32].…”
Section: Introductionmentioning
confidence: 99%